Локальная гипертермия в лечении злокачественных опухолей головного мозга; Вопросы онкологии; Т. 64, № 1 - Рябова А. И. Анастасия Игоревна; Грибова О. В. Ольга Вячеславовна; Новиков В. А. Валерий Александрович; Чойнзонов Е. Л. Евгений Лхамацыренович; Старцева Ж. А. Жанна Александровна; Милойчикова И. А. Ирина Алексеевна; Тургунова Н. Д. Наталья Джурабоевна; Васильев Р. В. Руслан Валерьевич (2018, 2018)
Заглавие с экрана